Controlled Release of A Poorly Water Soluble Drug Prednisolone from Heterodisperse Hydrogel System - GEETA AGGARWAL,; ARVIND SHARMA, (International Journal of Pharma and Bio Sciences, 2010)
The main objective of the present study is to prepare controlled release dosage form of prednisolone, a poorly water soluble drug. It is well known that certain moderate to poorly soluble drugs present difficulties, which render them incapable for sustained release formulations. To overcome this problem, a heterodisperse hydrogel system was formulated, which includes sustained release excipient including a gelling agent, an inert pharmaceutical diluent, an optional cationic cross linking agent and a poorly water soluble drug i.e. prednisolone. The results obtained indicated that acceptable 24 h release formulation may be obtained by this method.